One-Single Extraction Procedure for the Simultaneous Determination of a Wide Range of Polar and Nonpolar Organic Contaminants in Seawater - Fauvelle, Vincent; Castro-Jiménez, Javier; Schmidt, Natascha; Carlez, Benoit; Panagiotopoulos, Christos; Sempéré, Richard (Frontiers in Marine Science, 2018)
A rapid analytical method including one-single solid-phase extraction procedure followed by gas and liquid chromatography coupled with high resolution mass spectrometry detection (GC–MS and LC–HRMS respectively) was developed for the quantification of 40 polar and nonpolar organic compounds (1.6 < log Kow < 9.5) in seawater including both legacy and emerging contaminants, with a focus on the most common plastic organic additives. This new method allowed for the analyses of nine organophosphate esters (OPEs), seven phthalates (PAEs), six bisphenols (BPs), five perfluorinated compounds (PFCs), and thirteen legacy organochorinated compounds (OCs, including polychlorobiphenyles and pesticides) with recoveries in the ranges of 57–124 % for OPEs, 52–163 % for PAEs, 64–118 % for BPs, 63–124 % for PFCs, and 40–95 % for OCs. As a result of i) strict cleanup protocols, ii) material and solvent selection, and iii) the use of an ISO 6 cleanroom for sample treatment, the procedural blank levels were always lower than 5 ng L−1, even for the most abundant and ubiquitous compounds like tris-(2-chloro, 1-methylethyl) phosphate (TCPP) and diethylhexyl phthalate (DEHP). The quantification limits were in the ranges of 0.03–0.75 ng L−1 for OPEs, 0.03–0.25 ng L−1 for PAEs, 0.1–5 ng L−1 for BPs, 0.1–8 ng L−1 for PFCs, and 0.02–1.1 ng L−1 for OCs, matching seawater analysis requirements. Dissolved water phase samples collected in Marseille Bay (NW Mediterranean Sea) were analyzed using the developed method reveling the concentration of PAEs up to 140 ng L−1 (DEHP) and that of OCs up to 70 ng L−1 (α-endosulfan). For the first time, we also provided the concentrations of OPEs (TCPP up to 450 ng L−1), BPs (bisphenol S up to 123 ng L−1), and PFCs (PFOS up to 5 ng L−1) in this area. A sampling station close to the municipal waste water treatment plant outfall exhibited the highest concentration levels for all compounds.